Analysis of Storage Time for Merawang Chicken Eggs (Gallus Gallus) against Hatchability: A Systematic Review - Mafruchati, Maslichah; Makuwira, Jonathan (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
Background: Merawang chicken has the potential to be developed, both as local laying hens and local broilers. Hatchability and quality of hatching eggs are influenced by storage method, storage time, storage area, ambient temperature, incubator temperature, reversal during hatching. Storage that is too long causes the quality and hatchability to decrease so eggs should be stored no more than 7 days. Purpose: The purpose of this study was to analyze the length of storage of Merawang chicken eggs (Gallus gallus) on hatchability. Research methods: A literature search was carried out systematically through the PubMed, NCBI, Google Scholar databases using keywords, namely,